PENGARUH PENGETAHUAN, PENGALAMAN, SKEPTISME PROFESIONAL, DAN INTUISI DALAM MENDETEKSI KETIDAKTAATAN (Studi Empiris pada Inspektorat Provinsi NTB dan Kabupaten/ Kota se-Pulau Lombok) - Anton Kurniawan; Endar Pituringsih; Alamsyah Alamsyah (Jurnal Akuntansi Aktual, 2015)
This study aimed to examine the influence of the variables of knowledge, experience, profes-sional skepticism, and intuition government’s internal auditor on the ability to detect non-compliance.Research carried out on all of the government’s internal auditors who are at NTB Provincial Inspec-torate and the District/City in Lombok Island in 2015 with a number of 124 from 130 people auditors ofthe auditors that serve as a sample. The results showed that the ability of the government’s internalauditor is influenced by experience, professional skepticism, and intuition auditor. While the auditor’sknowledge which is defined as the level of education and formal and non-formal training does not affectthe auditor’s ability to detect non-compliance. This is because the formal education degree (S-1) is aformal requirement for a candidate to serve as auditor, other than that there is no specification ofspecial education requirements, the latter because of the difficulty of an auditor to keep abreast ofcontinuing education and training due to lack of budget and lack of training participants quota oftraining institutions. The implications of this research contributed to the development of science in thefield of public sector audit as a form of adoption agency theory, provide input for the Provincial Inspec-torate and district/city to improve the competence of auditors, and contribute to the Regional Govern-ment in formulating policies related to supervision over the Regional Government.Keywords: knowledge, experience, professional skepticism, intuition government’s internal auditor